К вопросу о гиперкатегориях - Лихaчевa, Д. Б. (Kalbotyra, 1988)
Two types of neutralization in morphology, singled out by analogy with the types in phonology, are discussed. The notion of the “hypercase” is introduced in this connection, which, as it is hoped, will contribute to a more profound understanding of the case.